Effect of Temperature and Prewetting for Ice Penetration with Sodium Formate. Issue 6 (June 2020) - Trzaskos, Mateusz Piotr; Klein-Paste, Alex
Granular sodium formate (NaCOOH) is a popular deicer used at airports. It is mainly used to weaken compacted snow/ice and thereby facilitate mechanical ice removal. Earlier research has developed a set of methods quantifying deicer performance, but linking these test results to operational guidelines is difficult. The main objective of this study is to increase the knowledge of how temperature and prewetting affect the ice penetration performance of granular sodium formate. A new method to evaluate the development of ice penetration process is presented here. Ice penetration tests were performed with single grains on large, optically clear ice cubes, and digital image analysis is used to quantify the initial waiting time, penetration rate and –depth, and melted volume. Eighteen tests including dry and prewetted sodium formate grains were performed at three different temperatures (–2°C, −5°C, and −10°C). Prewetting reduced the initial waiting time (the time it takes before the particles started to penetrate) by a few minutes at −10°C, but at higher temperatures, this reduction was insignificant. The particles penetrated the ice at a constant rate. At −10°C, the particles penetrated at 10–15 mm/hour, while at −2°C this speed is about five times higher. Prewetting does not seem to have a clear beneficial effect on the penetration rate. Suggestions are given on how to capture the results from this study into operational guidelines for deicing operations at airports, using sodium formate as deicer.